Pengembangan Aplikasi Sistem Informasi Antrian Online di Klinik Mekar Asri Menggunakan Model Waterfall - Muhammad Fahmi Febrian; Devina Azzahra Damayanti; Naufal Al Faruq; Yulianti Yulianti (Jurnal Informatika Universitas Pamulang, 2022)
Information systems are needed in this day and age, the rapid development of technology makes various human activities assisted by the system. The blooming asri clinic is a public health facility whose information system is still manual using paper documents. One activity that is still conventional is the queue at the clinic. The research method is structured for more structured and focused research activities in journal writing. There are several methods used in this research, including the following: Literature Study, Data Collection, Model Development, Online Queue Information System Application Development at Mekar Asri Clinic is very suitable when using the waterfall development model. With the online queuing application, of course, it makes it easier for health workers who are at the blooming beautiful clinic such as doctors, staff, receptionists etc. and also to improve the quality of service at the blooming beautiful clinic. This online queuing system application also makes it easier for patients if they want to go to the clinic without the need to come directly to take a queue number. With the online queuing application, of course, it makes it easier for health workers who are at the blooming beautiful clinic such as doctors, staff, receptionists etc. and also improve the quality of service. at the blooming beautiful clinic. This online queue information system application also makes it easier for patients if they want to go to the clinic without the need to come directly to take a queue number.Information systems are needed in this day and age, the rapid development of technology makes various human activities assisted by the system. The blooming asri clinic is a public health facility whose information system is still manual using paper documents. One activity that is still conventional is the queue at the clinic. The research method is structured for more structured and focused research activities in journal writing. There are several methods used in this research, including the following: Literature Study, Data Collection, Model Development, Online Queue Information System Application Development at Mekar Asri Clinic is very suitable when using the waterfall development model. With the online queuing application, of course, it makes it easier for health workers who are at the blooming beautiful clinic such as doctors, staff, receptionists etc. and also to improve the quality of service at the blooming beautiful clinic. This online queuing system application also makes it easier for patients if they want to go to the clinic without the need to come directly to take a queue number. With the online queuing application, of course, it makes it easier for health workers who are at the blooming beautiful clinic such as doctors, staff, receptionists etc. and also improve the quality of service. at the blooming beautiful clinic. This online queue information system application also makes it easier for patients if they want to go to the clinic without the need to come directly to take a queue number.